Primary liver cancer burden and its association with health development in the Western Pacific, 1990–2021 - Zhou, Teng-Chao; Qin, Dan; Yan, Peng; Lan, Bin; Wang, Qing; Tan, Jie (Frontiers in Oncology, 2025)
BackgroundLiver cancer (LC) is a major public health challenge in the Western Pacific Region (WPR), characterized by etiological diversity and increasing burden from both infectious and noninfectious causes. This study aimed to assess the burden of primary LC and its association with health system development indicators across the WPR from 1990 to 2021.MethodsWe conducted a secondary analysis using data from the Global Burden of Disease (GBD) Study 2021, covering 31 countries and territories in the WPR. LC burden was evaluated in terms of incidence, prevalence, mortality, and disability-adjusted life years (DALYs), stratified by sex, age, location, and five etiologies: hepatitis B virus (HBV), hepatitis C virus (HCV), alcohol use, nonalcoholic steatohepatitis (NASH), and other causes. Associations with Human Resources for Health (HRH), Universal Health Coverage (UHC) index, and Sociodemographic Index (SDI) were examined using Spearman correlation and generalized linear models.ResultsBetween 1990 and 2021, age-standardized DALYs rates for LC in the WPR rose from 281.78 to 334.74 per 100,000 population (EAPC: 0.56%). Total incidence nearly doubled, with sharp increases in Mongolia, Australia, and China. HBV remained the leading cause, while burdens from alcohol use and NASH grew markedly. LC burden showed moderate to strong positive correlations with HRH, UHC, and SDI, especially for HCV- and NASH-related cases; HBV-related burden showed weak associations.ConclusionsDespite progress in viral hepatitis control, the LC burden continues to rise in the WPR. Integrated strategies targeting viral, metabolic, and alcohol-related causes are urgently needed.